2018
DOI: 10.3389/fchem.2018.00292
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Desired Vertical Component Distribution Within a PBDB-T:ITIC-M Photoactive Layer via Fine-Tuning the Surface Free Energy of a Titanium Chelate Cathode Buffer Layer

Abstract: Rationally controlling the vertical component distribution within a photoactive layer is crucial for efficient polymer solar cells (PSCs). Herein, fine-tuning the surface free energy (SFE) of the titanium(IV) oxide bis(2,4-pentanedionate) (TOPD) cathode buffer layer is proposed to achieve a desired perpendicular component distribution for the PBDB-T:ITIC-M photoactive layer. The Owens-Wendt method is adopted to precisely calculate the SFE of TOPD film jointly based on the water contact angle and the diiodometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Therefore, γ s was evaluated using the O–W geometric equation method. [ 56–58 ] As shown in the images, the WCAs did not considerably differ. The hydrophobicity demonstrates the efficient charge transport between the active layers due to the effects of the halogenated atoms.…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, γ s was evaluated using the O–W geometric equation method. [ 56–58 ] As shown in the images, the WCAs did not considerably differ. The hydrophobicity demonstrates the efficient charge transport between the active layers due to the effects of the halogenated atoms.…”
Section: Resultsmentioning
confidence: 62%
“…(C) Three‐dimensional concentration profiles of S 2 − and CN − in the PBDB‐T:ITIC‐M blend films, and the TOPD layer is annealed at 90°C. Reproduced with permission: Copyright 2018, Frontier Media SA 141 (D) Pictures of IT‐4F thin films on glass, glass/ZnO, and glass/SnO 2 substrates under different‐time continuous UV illumination (365 nm, 5 mW cm −2 ).…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…It was found that optimum surface free energy (48.7 mJcm −2 ) close to IT‐M can achieve when the annealing temperature of titanium(IV) oxide bis(acetylacetonate) increased to 90°C resulting in the desired face distribution in the active layer based on PBDB‐T:ITIC‐M film which improves the photovoltaic parameters (Voc, Jsc, FF, and PCE) (Figure 6B,C). 141 Shi et al 153 used Ti(i‐OPr) 2 (acac) 2 as CIL in inverted NF‐OSCs. The PCE was increased from 9.6% to 11.7% benefiting from reduced charge recombination.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…For example, some electron-donating groups in organic sensitizer were successfully applied in porphyrin, such as N-annulated perylene ( 26 in Figure 4 ) (Jiao et al, 2011 ; Luo et al, 2013 , 2016 ), 2-diphenylaminothiophene ( 23 in Figure 4 ) (Wang et al, 2014d ), indoline ( 24 in Figure 4 ) (Pellej et al, 2014 ), phenothiazine ( 31 in Figure 4 ) (Xie et al, 2015 ), and even ferrocene (van der Salm et al, 2015 ). Some concepts from low-band-gap polymer were successfully applied in adjusting the absorption area and energy alignment of the porphyrins, such as weak donor-strong acceptor (Zhou et al, 2012 ; Bai et al, 2018 ; Lin et al, 2018 ; Xie et al, 2018 ), which will be discussed in the following part.…”
Section: The Development Of Porphyrins For Solar Cell Applicationmentioning
confidence: 99%